The Dynamics of Meaning in Life Among Older Adults Living Alone and Those Living with Family - Rohmah, Salsabilla Rofiatur; Ardelia, Vania (Character Jurnal Penelitian Psikologi, 2026)
Differences in older adults’ living arrangements shape how physical, emotional, and social needs are met, and they can influence quality of life and life satisfaction. Older adults who live alone may face greater risks of loneliness, limited access to day-to-day assistance, and declining well-being. In contrast, older adults who live with family often receive instrumental care, yet they do not always experience adequate emotional support and appreciation. This qualitative phenomenological study aimed to understand the dynamics of meaning in life among older adults living alone and those living with family. Six participants were recruited (three living alone and three living with family). Data were collected through semi-structured interviews, observations, and documentation, and were analyzed using Interpretative Phenomenological Analysis (IPA). The findings indicate that older adults’ meaning in life is constructed through self-acceptance, independence and productivity, gratitude and sources of happiness, spirituality, social relationships, contributions to others, and goals and future hopes. Dynamics of meaning in life are influenced not only by living arrangement but also by the primary anchor of meaning where older adults living alone tend to emphasize independence and local social networks, whereas those living with family tend to emphasize attachment and support within family relationships. Abstrak Perbedaan status hunian lansia memberikan dampak yang berbeda pada pemenuhan kebutuhan fisik, emosional, dan sosial, serta pada kualitas dan kepuasan hidup mereka. Lansia yang tinggal sendiri berisiko mengalami kesepian, keterbatasan akses bantuan, dan penurunan kualitas hidup, sementara lansia yang tinggal bersama keluarga mendapatkan perawatan namun tidak selalu merasakan dukungan emosional dan penghargaan yang memadai sehingga dari kondisi-kondisi ini menarik untuk melihat bagaimana lansia memaknai hidupnya. Tujuan penelitian adalah memahami dinamika makna hidup pada lansia yang tinggal sendiri dan lansia yang tinggal bersama keluarga. Penelitian menggunakan metode kualitatif fenomenologi dan enam partisipan dipilih terdiri dari tiga lansia yang tinggal sendiri dan tiga lansia yang tinggal bersama keluarga. Data dikumpulkan melalui wawancara semi-terstruktur, observasi dan dokumentasi kemudian dianalisis dengan teknik Interpretative Phenomenological Analysis (IPA). Hasil penelitian menunjukkan bahwa makna hidup lansia terbentuk melalui penerimaan diri, kemandirian dan produktivitas, rasa syukur dan sumber kebahagiaan, spiritualitas, hubungan sosial, kontribusi pada orang lain, tujuan serta harapan masa mendatang. Dinamika makna hidup lansia tidak hanya dipengaruhi oleh status hunian, tetapi pada titik tumpu makna dimana lansia yang tinggal sendiri lebih menekankan pada kemandirian dan jejaring sosial sekitar, sementara lansia yang tinggal bersama keluarga lebih menekankan kelekatan dan dukungan dalam hubungan dengan keluarga.